Can Environmental Information Disclosure Improve Urban Green Economic Efficiency? New Evidence From the Mediating Effects Model - Lin, Shihai (Frontiers in Environmental Science, 2022)
Environmental information disclosure is one of the important ways to realize urban sustainable development. This study explores the transmission mechanism between environmental information disclosure and urban green economic efficiency (UGEE) and solves the “black box” system between them. In this method, first, the urban green economic efficiency is calculated using the data envelopment analysis model with undesirable output. Second, the panel data model and the mediating effects model are employed to test the impact of environmental information disclosure on urban green economic efficiency and the possible mediating variables. The main conclusions of this study are as follows: 1) Environmental information disclosure significantly improves urban green economic efficiency, and reducing industrial pollutant emission and improving technological innovation are the significant transmission mechanisms. (2) There is a U-shaped curve relationship between environmental information disclosure and urban green economic efficiency and environmental information disclosure and technological innovation. On the contrary, there is an inverted U-shaped curve relationship between environmental information disclosure and industrial pollutant emission. 3) Environmental information disclosure has a greater sustainability effect in industrial cities. The conclusion shows that environmental information disclosure can improve the efficiency of urban green economy by improving the ability of urban technological innovation and reducing the emission of industrial pollutants. Environmental information disclosure plays a role of “restraining first and then promoting” to sustainable development. This research provides a reference for how to lessen information asymmetry and reduce negative externalities in the formulation of environmental regulatory policies.